Topically applied bacteriophage to control multi-drug resistant Pseudomonas aeruginosa-infected wounds in a New Zealand rabbit model - Wang, Jinyu; Meng, Wenxin; Zhang, Kaichuan; Wang, Jingyu; Lu, Baochun; Wang, Ruijie; Jia, Kun (Frontiers in Microbiology, 2022)
Pseudomonas aeruginosa (P. aeruginosa) is a widespread, gram-negative, pathogenic bacterium that causes serious internal and external infections in humans and other animals. The increasing antibiotic resistance has complicated bacterial infection treatment, and current antibiotic therapies cannot cure all infections. Owing to this, bacteriophages (phages) have regained attention as potential therapeutics for bacterial infections. In this study, the phage “PaVOA” was isolated from hospital sewage and characterized. Next, a New Zealand rabbit skin infection model was used to determine the therapeutic efficacy of PaVOA as compared to a phage cocktail or the cephalosporin antibiotic ceftriaxone. Characterization results demonstrated that phage PaVOA belongs to the Myoviridae family, has a double-stranded DNA genome, is resistant to low temperatures (-20 °C), is most optimal at 40 °C, has good acid-base tolerance, and remains stable for 30 min under 20 W ultraviolet (UV) intensity. The optimal MOI of PaVOA was 0.1, and a one-step growth curve showed a short latency period (10 min), thus demonstrating its ability to rapidly kill bacteria. Furthermore, the addition of calcium (Ca) and magnesium (Mg) ions significantly increased the PaVOA titer. An in vivo phage kinetic curve showed that PaVOA was rapidly inactivated within the blood of New Zealand rabbits (undetectable after 12 h), and no animals died due to phage treatment. Wound healing studies showed that the phage cocktail induced a high healing rate and an acceleration of the skin remodeling process, and was more efficacious than ceftriaxone. Therefore, phage cocktail therapy represents a novel therapeutic approach in the treatment of traumatic skin infections caused by multi-drug resistant P. aeruginosa.